Perbedaan Aldrete Score Akibat Penggunaan Halotan dan Sevofluran - Rinanto, D. Purbo; Supraptomo, R.Th; Wicaksono, Bagus (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background : Inhaled Anesthesia is anesthesia drugs in the form of gas or volatile liquid that is given through the respiratory patient . This anesthesia has the advantage of high potency and concentration that can be controlled through the engine . Inhaled anesthetics commonly used in surgery are halothane and sevoflurane . The main concern is the safety of anesthesia and patient safety , and one of them includes the recovery of consciousness and regular use Aldrete score . This study aims to determine the effect of the difference Aldrete score inhaled anesthetics halothane and sevoflurane. Methods: This study was an observational analytic study using cross - sectional study with subjects surgery patients with inhalation anesthetics halothane and sevoflurane in the Instalasi Bedah Sentral ( IBS ) RSUD Dr. Moewardi Surakarta . With quota sampling technique, this study obtained 40 sampels, which consisted of 20 patients with halothane anesthesia , and 20 patients with sevoflurane anesthesia . Data were collected by observation in the post-operative and medical records room . Data were analyzed using independent t-test, the homogeneity test and comparison test average. The data were processed with the Statistical Product and Service Solutions ( SPSS )18.00Â for Windows. Results : Data were tested by independent t-test , showed average values ââfor halothane group was 9.2 , while the average value for the sevoflurane group was 9.0. However , the value obtained Sig ( 2 - tailed ) ( 0.151 ) > Î± ( 0.05 ) so that Ho is accepted . Or it can be concluded that there was no significant difference between the average value Aldrete score halothane and sevoflurane groups . Value Std . Error Difference also showed the same value is 0.066 so that there was no significant difference in the two groups . Conclusions : Both groups had an average value of the same or there is no significant difference between the two groups either inhaled anesthetics halothane and sevoflurane Keywords : inhalation anesthetics , halothane , sevoflurane , level of consciousness, Aldrete score Â